PENGALAMAN GURU DALAM MENGIDENTIFIKASI DAN MENANGANI GANGGUAN JUGA PENYIMPANGAN PERKEMBANGAN SISWA SEKOLAH DASAR: STUDI FENOMENOLOGI - Fitriah Khoirul Umamah; Titin Nurhidayati (As-Sulthan Journal of Education, 2026)
This study aims to explore teachers' experiences in identifying and addressing developmental disorders and deviations in elementary school students at SDN Kencong 01. The study used a qualitative approach with a phenomenological design to understand the meaning of teachers' pedagogical experiences in the context of everyday learning. Data were collected through in-depth interviews with fifth-grade teachers, observations of the learning process, and analysis of supporting documents. Data were then analyzed using data reduction, thematic coding, and extracting essential meanings. Data validity was ensured through triangulation of sources and techniques. The results showed that teachers play a role as early detectors of developmental disorders and deviations in students through contextual observations of their learning behavior, social interactions, and emotional regulation. The identification process is more intuitive and based on pedagogical experience than formal assessment. In handling, teachers apply a responsive pedagogical approach through adjustments to learning strategies, individual attention, and emotional approaches. However, the effectiveness of these efforts is limited by specific competencies, minimal institutional support, and the absence of supporting professionals in regular public elementary schools. This study concludes that teachers' experiences are an important source of contextual pedagogical knowledge, but require strengthening through school support systems, ongoing training, and structured collaboration with parents. These findings contribute to the development of more inclusive and equitable basic education practices.